CCNA portable command guide - Empson, Scott (Cisco Press, 2007)
CCNA Portable Command Guide Second Edition All the CCNA 640-802 commands in one compact, portable resource Preparing for the CCNA® exam? Here are all the CCNA-level commands you need in one condensed, portable resource. The CCNA Portable Command Guide, Second Edition, is filled with valuable, easy-to-access information and is portable enough for use whether you're in the server room or the equipment closet. This book has been completely updated to cover topics in the ICND1 640-822, ICND2 640-816, and CCNA 640-802 exams. Use this quick reference resource to help you memorize commands and concepts as you work to pass the CCNA exam. The guide summarizes all CCNA certification-level Cisco IOS® Software commands, keywords, command arguments, and associated prompts, providing you with tips and examples of how to apply the commands to real-world scenarios. Configuration examples throughout the book provide you with a better understanding of how these commands are used in simple network designs. The ten topics covered are TCP/IP An Introduction to Cisco Devices Configuring a Router Routing Switching Implementing a Wireless LAN Network Administration and Troubleshooting Managing IP Services WANs Network Security Scott Empson is currently the associate chair of the bachelor of applied information systems technology degree program at the Northern Alberta Institute of Technology in Edmonton, Alberta, Canada, teaching Cisco® routing, switching, and network design courses in certificate, diploma, and applied degree programs at the post-secondary level. He is also the program coordinator of the Cisco Networking Academy® Program at NAIT, a Regional Academy covering central and northern Alberta. He has earned three undergraduate degrees and currently holds several industry certifications, including CCNP®, CCDA®, CCAI, and Network+®. Access all CCNA commands-use as a quick, offline resource for research and solutions Logical how-to topic groupings provide one-stop research Great for review before CCNA certification exams Compact size makes it easy to carry with you, wherever you go "Create Your Own Journal" section with blank, lined pages allows you to personalize the book for your needs "What Do You Want to Do?" chart inside back cover helps you to quickly reference specific tasks This book is part of the Cisco Press® Certification Self-Study Product Family, which offers readers a self-paced study routine for Cisco® certification exams. Titles in the Cisco Pr ...
Print version record
Keywords: Computer networks -- Study guides -- Examinations; Internetworking (Telecommunication) -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Réseaux d'ordinateurs; Examens; Guides de l'étudiant; Interconnexion de réseaux (Télécommunications); Examens; Guides de l'étudiant; Computer networks; Examinations; Study guides; Internetworking (Telecommunication); Examinations; Study guides; Electronic data processing personnel; Certification; Computer networks; Examinations; Internetworking (Telecommunication); Examinations; examination study guides; Study guides; Guides de l'étudiant